Server-based open system implementation for ICOSYS (ICOSYS2) - Hassan, Suhaidi; Mohd Shabli, Ahmad Hanis; Ahmad, Amran; Azzali, Fazli; Yahya, Noor Izzah (Universiti Utara Malaysia, 2005)
Information and communication services are developed to enhance the utilization of the ICT infrastructure.These services can be implemented either using proprietary or open source software platforms.This work focuses on the implementation of the open source services at the Faculty of Information Technology (FTM), Universiti Utara Malaysia. The study is part of the ICOSYS research intitiative.The underlying vision of ICOSYS2 is to create a conducive and efficient working environment using open source technologies.ICOSYS2 consists of four basic services that comprises file storage, application, printing and backup services.Firstly, ICOSYS2 files and storage services provide users with the ability of centrally storing and sharing data.Secondly, the ICOSYS2 application services provide access to the world of Linux-based open source applications.Thirdly, ICOSYS2 printing services allow users to send their print jobs to respective printers across the FTM network and pave the way for centralized printing administration.Finally, the ICOSYS2 backup services outlines a tertiary mean to backup the users' data.It is hoped the implementation of this ICOSYS2 project can facilitate academic and administrative tasks at FTM.